PENGEMBANGAN P4 (PRODUCT, PRICE, PLACE, PROMOTION) KEMPLEE (KEMPLANG LELE) PADA UMKM ANUGERAH LELE - Anita, Sumarni Bayu; Mayreista, Dita; Arif, Abdurrahman (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2024)
P4K KEMPLEE stands for P4 Development (Product, Price, Place, Promotion) Kemplang LeleEntrepreneurship. P4K KEMPLEE is the big theme for the STISIPOL Candradimuka ThematicReal Work Lecture (KKNT) 2020 chosen by Group 10 to be implemented at the selected KKNlocation, namely the UMKM Lele Anugerah in Pulau Harapan Village, Sembawa, Banyuasin,South Sumatra. The theme that can learn about the world of entrepreneurship is more challengingto apply because students can learn and try to apply the theories they get in college to help UMKMAnugerah Lele further develop their business. Development of the 4P or P4 Concept in theMarketing Mix, namely Product, Place, Price, Promotion, was chosen as the main theory in theimplementation of KKNT SC Group 10. Based on Creswell (2010), this research includes aqualitative approach because it wants to understand how the rePlaatiolensmhipb abnetgween the implementation of the Thematic Real Work Lecture (KKNT) STISIPOL Candradimuka which wa carried out during 1-31 December 2020 with P4 Development (Product, Price, Place, Promotion) Entrepreneurship of Kemplang Lele at UMKM Anugerah Lele in Pulau Harapan Village, Sembawa, Banyuasin. From the results of the analysis, it was found that the theme of Independent Entrepreneurship would be very effective in its development by demanding the activeness of Field Supervisors (DPL) in guiding and assigning assignments to students. KKNT Group 10 students is well offered community service programs that are effectively implemented at the UMKM Anugerah Lele under the name Panca Action KKNT SC 10, (1) Namely naming brands, (2) Making product logos, (3) Creating social media accounts, (4) Conducting entrepreneurship seminars, and (5) Provision of production facilities assistance.